Ratty tattletale - LaReau, Kara (LaReau, Kara. Infamous Ratsos., 2021)
Ralphie stands up to two bullies for picking on his mouse friend Tiny. He is encouraged to tell an adult but doesn't want to be thought of as a tattletale. Ralphie's father, Big Lou, teaches him that doing what is right is more important than doing what is cool.